2007
DOI: 10.1002/jtr.644
|View full text |Cite
|
Sign up to set email alerts
|

Gaining residents' support for tourism and planning

Abstract: This research analyses residents' perceptions of the effects of tourism. Economic, cultural and environmental effects are identified as determinants of residents' attitudes towards tourism development and planning. Authors speculate that there are different patterns of resident's support depending on their differential benefits obtained from tourism. A conceptual model is developed and empirically tested in Santiponce, a small community in southern Spain. Our results support our basic hypothesis: resident's le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(75 citation statements)
references
References 58 publications
7
55
0
7
Order By: Relevance
“…This situation is supported by previous studies by [27-28, 30, 35]. Review by Oviedo-Garcia et al [35] found that the local population of Santipoce giving their views positively rather than negatively in which they receive benefits from tourism activities in their area while supporting the development project. Western scholar also stressed that local population positive outlook on the development of tourism is an important point and may have a positive impact on the planning of tourism development [35,[45][46][47].…”
Section: Conclusion and Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This situation is supported by previous studies by [27-28, 30, 35]. Review by Oviedo-Garcia et al [35] found that the local population of Santipoce giving their views positively rather than negatively in which they receive benefits from tourism activities in their area while supporting the development project. Western scholar also stressed that local population positive outlook on the development of tourism is an important point and may have a positive impact on the planning of tourism development [35,[45][46][47].…”
Section: Conclusion and Discussionsupporting
confidence: 79%
“…Review by Oviedo-Garcia et al [35] found that the local population of Santipoce giving their views positively rather than negatively in which they receive benefits from tourism activities in their area while supporting the development project. Western scholar also stressed that local population positive outlook on the development of tourism is an important point and may have a positive impact on the planning of tourism development [35,[45][46][47]. Murphy [38] has emphasized that community input and participation in tourism planning should be taken into account so that the mission of the tourism project can be achieved.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, improved collaboration, integrated but centralized steering of action, and innovation to transform the economy Single destinations may collaborate with other destinations, developing a larger destination network governed by a collectively financed DMO. At the same time, they continue to maintain strong individual municipalities, leading to economic benefits but also to changes in local identity and culture (e.g., Oviero-Garcia et al 2008, Pechlaner et al 2012. Destination governance is dependent on the network of actors delivering a number of products and services (Ruhanen et al 2010, Presenza and Cipollina, 2010, Haugland et al 2011, while destination success, as well as that of individual actors, is dependent, among other aspects, on governing complex networks (Beritelli et al 2007).…”
Section: Climate Change In the Surselva-gotthard Regionmentioning
confidence: 99%
“…The first research area focused on the environmental, economic and the socio-cultural impacts of tourism (Archer et al, 2005;Mason, 2003;Oviedo-Garcia et al, 2008;Swarbrooke, 1999). These authors stress some positive and negative impacts of tourism on the identity of urban heritage places.…”
Section: Urban Identity and Tourismmentioning
confidence: 99%